CO2 Emissions from Tropical Peat Soil Affected by Fertilization - Husnain, .; Sipahutar, Ibrahim Adamy; Purnomo, Joko; Widyanto, Hery; Nurhayati, . (UNIVERSITY OF LAMPUNG, 2017)
The conversion of peat soils to agricultural uses has been thought to increase CO2 emission due to several factors, including fertilization. However, evidence on the effect of fertilization on CO2emissionsfrompeat soils is rareand often inconsistence. We measured the effects of different types of fertilizer, including N, P and K sources, and clay as an ameliorant on CO2 emission from a bare peat soil in Lubuk Ogong, Riau Province. Nutrients were added in the following combinations: 0 (unfertilized plot), N source (urea), slow-release N (slow release urea), N and Psource (Urea+SP-36), N, P and K sources (urea+SP-36+KCl) and combined NPK-Clay. Fertilization resulted in a decreasein CO2 emissions compared to that prior to fertilization except when slow-release urea was applied. Decreasing of CO2 emissions was probably due to pH-related effects because the pH in the N treatment was lower than in both the control and the unfertilized plot. A decreasein the level of CO2 emissions among the treatments followed the order NPK-Clay>NP>NPK>urea>slow-release urea. Covariance analyses showed that the difference in CO2 emissions prior to treatment was not significant. The application of individual and combined treatments of N, P, K and NPK mixed with 5 Mg ha-1 clay led to significantly reduced CO2 emissions from bare peat soil in Lubuk Ogong, Riau Province. In addition to fertilization, the water table depth was the only parameter that significantly affected the CO2 emissions (P<0.05). We conclude that the application of nutrient combinations, including N, P, K and clay, could reduce CO2 emissions because these treatments maintain a balanced nutritional condition in the soil with respect to the microbial activity.Keywords: Amelioration, CO2 emission, fertilization, tropical peat soilsÂ Â Â